2022
DOI: 10.1039/d2sc03074h
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility is the key to tuning the transport properties of fluorinated imide-based ionic liquids

Abstract: The interplay of fluorination, flexibility, and mass affects the transport properties of imide ionic liquids. Here we show how the combination of experimental and theoretical techniques can disentangle such confounding variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 103 publications
2
28
0
Order By: Relevance
“…Our most notable finding from crystal analysis is that TFSI anions exist as an unsymmetric conformer in a higher electronic energy state in [AdImMe][TFSI], as compared to TFSI in typical ionic liquids. [39][40][41][42] This unexpected conformer is stabilized by the diamondoid-templated lattice and does not change as lithium concentration increases as confirmed via Raman spectroscopy (Fig. 3) and 19 F NMR (Fig.…”
Section: Of Mixtures Containing [Adimme][tfsi] and [Li][tfsi] Do Not ...mentioning
confidence: 57%
“…Our most notable finding from crystal analysis is that TFSI anions exist as an unsymmetric conformer in a higher electronic energy state in [AdImMe][TFSI], as compared to TFSI in typical ionic liquids. [39][40][41][42] This unexpected conformer is stabilized by the diamondoid-templated lattice and does not change as lithium concentration increases as confirmed via Raman spectroscopy (Fig. 3) and 19 F NMR (Fig.…”
Section: Of Mixtures Containing [Adimme][tfsi] and [Li][tfsi] Do Not ...mentioning
confidence: 57%
“…73–75 The increased void space in 3 could account for the complex thermal behavior observed, given the more accessible motion of the molecules and anions ( vide infra ). 76 Particularly within this set of molecules, it is observed that the imidazolium heterocycle can rotate, vis-à-vis the observed disorder in 4 , allowing of distinct orientations of the cationic head.…”
Section: Resultsmentioning
confidence: 92%
“…The low dynamic viscosities of the TFSI-ILs nicely agree with this argument because the TFSI anion is the least rigid, most exible one in the series studied, herein. 21,23 If ion mass and size (Table 2) were the most relevant factors determining the dynamic viscosity, the TFSI-ILs would have properties in between those of the respective ILs with the anions 4cPFSI and 5cPFSI.…”
Section: Viscosities and Conductivitiesmentioning
confidence: 99%
“…20 A further properties determining factor is the conformational exibility of the ions as a higher number of conformers increases the entropy of the liquid. 4,[21][22][23][24] So, the introduction of exible alkyl chains is a common strategy for the design of low-melting ILs, e.g. in 1-alkyl-3methylimidazolium ions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation